Introducción al concepto de derivados financieros y su manejo en Colombia (Revista "Boletín el Conuco", 2020)
The market of financial instruments dating back to the era before Christ, and despite their remote origin can be said that its boom began in the Decade of the ‘ 70s, thanks to the model of valuation of financial derivatives, known as the model of Black-Scholes-Merton, which enabled its evaluation and encouraged its use by investors in financial for whom it is a valuable tool. Around the world, have been the subject of widespread criticism, even to be designated as the cause of great financial crisis originated in the developed countries. In Latin American markets Brazil as the leader of the derivatives market, and Mexico as a duly self-regulated growth market. In the Colombian case, it should be mentioned that the derivative market is just in its initial stage, with relatively prudent use, in addition to deemed that the information emerged on the subject is scarce and concentrated in Government as theBolsa de Valores de Colombia and the FinancialSupervisory Authority.The objective of this work is to generate a document of academic type that allows you to introducing to not knowledgeable on the subject, which is extremely interesting and useful tool in the economic and commercial context of the country. This has been determined using a methodology of research of exploratory type, which is useful when there is no exact investigation on the matter.
Keywords: financial instruments; financial market; derivatives